Aktivitas Antiinflamasi Topikal Sediaan Facewash Ekstrak Daun Pepaya (Carica papaya L.) pada Model Edema Terinduksi Karagenan pada Tikus - Ananda Ramadani; Ronal Ronal (Jurnal Kesehatan Yamasi Makassar, 2026)
Papaya leaves (Carica papaya L.) have long been used as a traditional medicine due to their bioactive compounds that have anti-inflammatory potential. Edema is a form of inflammatory response characterized by fluid accumulation in interstitial tissue due to increased vascular permeability. This study aims to evaluate the anti-edema effect of a facewash containing papaya leaf extract on the back skin of white rats (Rattus norvegicus). This study was a laboratory experimental study with a completely randomized design. Edema was induced using a 3% carrageenan suspension subcutaneously on the back skin of rats. Skinfold thickness was measured using a caliper before treatment (T₀) and after induction at certain time intervals. Rats were divided into several treatment groups given papaya leaf extract facewash with concentrations of 5%, 10%, and 20%. The results showed that the papaya leaf extract facewash had anti-edema activity with a decrease in skinfold thickness compared to the control. The 10% concentration showed the highest edema-reducing effect at 9%, followed by the 20% concentration at 5%, and the 5% concentration at 3%. Based on these results, it can be concluded that the papaya leaf extract face wash has potential as a topical anti-inflammatory agent, with an optimum concentration of 10%.